Indirect Transmission of Escherichia coli O157:H7 Occurs Readily among Swine but Not among Sheep - Cornick, Nancy A. (American Society for Microbiology (ASM), 2008)
Transmission of Escherichia coli O157:H7 among reservoir animals is generally thought to occur either by direct contact between a naïve animal and an infected animal or by consumption of food or water containing the organism. Although ruminants are considered the major reservoir, there are two reports of human infections caused by E. coli O157:H7 linked to the consumption of pork products or to the contamination of fresh produce by swine manure. The objective of this study was to determine whether E. coli O157:H7 could be transmitted to naïve animals, both sheep and swine, that did not have any direct contact with an infected donor animal. We recovered E. coli O157:H7 from 10/10 pigs with nose-to-nose contact with the infected donor or animals adjacent to the donor and from 5/6 naïve pigs that were penned in the same room as the donor pig but 10 to 20 ft away. In contrast, when the experiment was repeated with sheep, E. coli O157:H7 was recovered from 4/6 animals that had nose-to-nose contact with the infected donor or adjacent animals and from 0/6 naïve animals penned 10 to 20 ft away from the donor. These results suggest that E. coli O157:H7 is readily transmitted among swine and that transmission can occur by the creation of contaminated aerosols.